Perception of Professional Accountants about the Application of Artificial Intelligence (AI) in Auditing Industry of Bangladesh - Afroze, Dilruba; Aulad, Anisha (Journal of Social Economics Research, 2020)
Globalization and frequent evolution of technology keeps putting pressure on professionals mastered in different fields which does not leave accountants and auditing professionals behind. With frequent adoption of modern technologies like AI, it has become incumbent on every professional to adopt and regularize the use of such technologies in respective fields. Accounting and auditing, previously a tedious work, has become faster and easier through technologies like knowledge based systems. Although the concept of AI is relatively new in the world of accounting, it is being used extensively by some firms and practitioners and continues to evolve its ways. However, within the context of Bangladesh, the application of AI is still in its infant’s stage. This study aims at exploring the perceptions of accounting professionals about the application of AI in their profession. Respondents of this study are audit practitioners employed in different auditing firms across Dhaka city. We have collected data through five point Likert scale and a questionnaire survey. We have found a variety of perceptions about this technology from the practitioner’s. Result indicates that professionals in Bangladesh still are not fully aware of AI use in auditing. Certain problems like incurrence of huge cost, lack of information security and unsecured jobs create hindrance for AI to get rooted in the auditing industry of Bangladesh.